Pengaruh Budaya Organisasi, Karakteristik Kerja, dan Stres Kerja, Serta Dampaknya Pada Kinerja Pegawai (Studi Pada PT. PLN (Persero) AP2B Sistem Minahasa - Pamungkas, Dany Galih (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The purpose of this research is to examine the influence of organization culture, job characteristics, and job stress to staff performance in PT PLN (Persero) AP2B system Minahasa. The result show the organization culture has not significantly effect to job stress, job characteristics has a significantly effect to staff performance, and job stress has not significantly effect to staff peformance.Keywords: Organization Culture, Job Characteristics, Job Stress, Staff Performance